2011
DOI: 10.1007/s11121-010-0192-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Efficacy of Click City®: Tobacco: Changing Etiological Mechanisms Related to the Onset of Tobacco Use

Abstract: This paper described the short-term results from an ongoing randomized controlled efficacy study of Click City ® : Tobacco, a tobacco prevention program designed for 5 th graders, with a booster in sixth grade. Click City ® : Tobacco is an innovative school-based prevention program delivered via an intranet, a series of linked computers with a single server. The components of the program target theoretically based and empirically supported etiological mechanisms predictive of future willingness and intentions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 46 publications
1
32
1
Order By: Relevance
“…The PWM has been used as the basis for interventions which have shown promise in targeting risk behaviours, for example increasing condom use (Blanton et al, 2001) and reducing willingness to smoke (Andrews et al, 2011). Less research however, has explored the PWM in relation to adolescent drinking in the United Kingdom (UK), and no existing preventive interventions targeting this specific population have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…The PWM has been used as the basis for interventions which have shown promise in targeting risk behaviours, for example increasing condom use (Blanton et al, 2001) and reducing willingness to smoke (Andrews et al, 2011). Less research however, has explored the PWM in relation to adolescent drinking in the United Kingdom (UK), and no existing preventive interventions targeting this specific population have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Health behavior cognitions have been shown to be modifiable (Andrews, Gordon, Hampson, Christiansen, Gunn, Slovic & Severson, 2010; Andrews, Hampson & Gordon, 2009; Sussman, 1989) and thus are important etiological mechanisms to target in prevention programs. However previous research has not linked health behavior cognitions regarding alcohol use in early adolescence to heavy drinking in mid adolescence, when youth are aged 14 to 18.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies by Andrew et al in 2011 and 2014 which analyzed the short and long term efficacy of "Click city tobacco intervention" found that the intervention had the potential to significantly postpone or prevent the initiation of cigarette use and regular smoking among students. However, while in the short term the intervention showed moderate effectiveness at changing intentions to use smokeless tobacco in the future, the effect did not persist in the long term [46,58]. Another study, (Deitz et al, 2011) which evaluated the effect of the Smart Rx web program found that it significantly increased participants' knowledge of proper prescription drug use, and improved their selfefficacy in ability to manage and adhere to appropriate treatments [33].…”
Section: Outcomes and Resultsmentioning
confidence: 99%